2008
DOI: 10.1021/jp806963u
|View full text |Cite
|
Sign up to set email alerts
|

Relating Conformation and Photophysics in Single MEH-PPV Chains

Abstract: We use a novel fluorescence polarization microscope in combination with molecular dynamics calculations to determine the conformation of individual isolated chains of the conjugated polymer MEH-PPV. We found a narrow distribution of defect cylinder conformations in a poor-solvent matrix and two types of defect coil conformations in a good-solvent matrix. The conformations were related to photophysical properties of MEH-PPV by measuring fluorescence intermittency on the same chains. We obtained direct evidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
107
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 98 publications
(115 citation statements)
references
References 27 publications
6
107
1
1
Order By: Relevance
“…Th is has been demonstrated using a combination of polarization-modulated epi-fl uorescence and total internal refl ection illumination with a widefi eld microscope [20]. It has thus been found that irrespective of conformation, MEH-PPV chains tend to orient parallel with the sample substrate during the spin-coating sample preparation process [15].…”
Section: Optical Measurement Of Conformation and Orientation Of A Sinmentioning
confidence: 97%
See 2 more Smart Citations
“…Th is has been demonstrated using a combination of polarization-modulated epi-fl uorescence and total internal refl ection illumination with a widefi eld microscope [20]. It has thus been found that irrespective of conformation, MEH-PPV chains tend to orient parallel with the sample substrate during the spin-coating sample preparation process [15].…”
Section: Optical Measurement Of Conformation and Orientation Of A Sinmentioning
confidence: 97%
“…In addition to the projection onto the sample plane, this method uses polarization-modulated total internal refl ection illumination to measure the projection of the ellipsoid in a plane perpendicular to the sample (Figure 3(b)). Th is method has been used to measure the absorption ellipsoids of MEH-PPV in various polymer matrices [15]. Th e conformation of individual chains must still be reconstructed by molecular dynamics simulations, but the conformation is now available for each polymer chain individually, thus making it possible to study the conformation and properties on a truly single-molecule level.…”
Section: Optical Measurement Of Conformation and Orientation Of A Sinmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Recently, we reported a novel fluorescence polarization microscopic method 6 and used it together with molecular dynamics simulations to reveal the conformation of individual polymer chains on a truly single-molecule level. 7 This enabled us to study photophysical properties of MEH-PPV on the same single chains and to show that the conformational state is the determining factor for the photophysical processes. Here, we use the previously determined conformations of MEH-PPV in different host matrices and correlate the structural information with single chain emission spectra.…”
Section: 4mentioning
confidence: 99%
“…Previous studies have revealed that there are two main fluorescence time transients in MEH-PPV single molecules, corresponding to collapsed and extended chain conformations. 14,15 A collapsed chain displays discrete fluorescence blinking due to a disruption of the energy transfer pathway to the emitting chromophore by the formation of a long-lived absorbing state or by transient bleaching of the emitting chromophore through said long-lived state. 10 In contrast, an extended chain exhibits continuous photobleaching as one chromophore after another photo-oxidises.…”
mentioning
confidence: 99%